2002
DOI: 10.2172/805151
|View full text |Cite
|
Sign up to set email alerts
|

Building-related symptoms among U.S. office workers and risks factors for moisture and contamination: Preliminary analyses of U.S. EPA BASE Data

Abstract: Background: We assessed relationships between health symptoms in office workers and risk factors related to moisture and contamination, using data collected from a representative sample of U.S. office buildings in the U.S. EPA BASE study.Methods: Analyses assessed associations between three types of weekly, workrelated symptoms -lower respiratory, mucous membrane, and neurologic -and risk factors for moisture or contamination in these office buildings. Multivariate logistic regression models were used to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…from 80 complaint office buildings, controlling for many more confounders, and only debris in the outdoor air intake and poor drainage in cooling drain pans remained significant predictors of symptoms. A similar analysis, but in 100 non‐complaint office buildings (Mendell & Cozen 2003b), found that less frequent air‐handler inspection was associated with increased symptoms; however, dirty cooling coils, dirty drain pans with poor drainage, and standing water near outdoor intakes were not associated with significant increases in symptoms.…”
Section: Operation and Maintenancementioning
confidence: 83%
“…from 80 complaint office buildings, controlling for many more confounders, and only debris in the outdoor air intake and poor drainage in cooling drain pans remained significant predictors of symptoms. A similar analysis, but in 100 non‐complaint office buildings (Mendell & Cozen 2003b), found that less frequent air‐handler inspection was associated with increased symptoms; however, dirty cooling coils, dirty drain pans with poor drainage, and standing water near outdoor intakes were not associated with significant increases in symptoms.…”
Section: Operation and Maintenancementioning
confidence: 83%
“…In a nationwide study of 100 buildings not known to have indoor air quality complaints, current water damage was documented in 43% (11). Although the prevalence of indoor dampness is variable depending on the country, continent, and climate zone, the World Health Organization (WHO) estimated that from 10% to 50% of indoor environments are affected by damp conditions in Europe, North America, Australia, India, and Japan (12).…”
Section: Introductionmentioning
confidence: 99%